Hypersensitivity of Vestibular System to Sound and Pseudoconductive Hearing Loss in Deaf Patients. (3rd March 2014) - Emami, Seyede Faranak
Abstract : The objective of this cross-sectional study is to compare bone-conducted low-frequency hearing thresholds (BClf) to cervical vestibular evoked myogenic potentials (cVEMPs) findings in prelingual adult deaf patients. The fifty participants (100 ears) included twenty healthy controls and thirty other subjects selected from patients who presented with bilateral prelingual deafness to Department of Audiology of Hamadan University of Medical Sciences and Health Services (Hamadan, Iran). Assessments comprised of audiological evaluations, cVEMPs, and computerized tomography scans. Twenty deaf patients ( forty affected ears ) with bilateral decreased vestibular excitability as detected by abnormal cVEMPs revealed that BClf hearing thresholds were completely absent. Ten deaf patients ( twenty unaffected ears ) with normal cVEMPs reported a sensation of the sound at BClf hearing thresholds (the mean for250 Hz = 41  dBHL and for500 Hz = 57.75  dBHL ). Multiple comparisons of mean p 13 latencies, mean n23 latencies and peak-to-peak amplitudes between three groups were significant ( P = 0.01 for all, one-way ANOVA test). Multiple Comparisons of mean BClf between three groups were significant ( P = 0.00, One-way ANOVA test). Conclusion . Hypersensitivity of vestibular system to sound augments BClf hearing thresholds in deaf patients. The sensation of the sound at low frequencies may be present in patients with total deafness and normal vestibular function (predominantly saccule). This improvement disappears when saccular function is lost.